Improved conditions for the aerobic reductive decolourisation of azo dyes by Candida zeylanoides - Ramalho, Patrícia Alexandra Costa Ferreira (2002)
A number of anaerobic and aerobic bacterial species are known to decolourise azo dyes through the reduction of the azo bonds, forming the corresponding amines. In this work, we describe improved decolourisation conditions for model azo dyes by the ascomycete yeast Candida zeylanoides. The dyes were derived from the diazonium salts of metanilic and sulfanilic acids and N,N-dimethylaniline or 2-naphthol as coupling components. Total decolourisation times observed in culture media supplemented with 0.2mM dye ranged from 40 go 60 hours. The initial decolourisation rates were 14-52µmol.(g dry cell)-¹.h-¹, depending on dye structure. In the course of decolourisation either metanilic acid or sulfanilic acid were detected in the supernatant fluid, showing that decolourization by this yeast strain is due to azo bond reduction. None of those aminobenzenesulphonates supported microorganism growth as carbon and energy source but both could be used, to a limited extent, as nitrogen sources. The azo reductase activity is not significantly affected by pre-adaptation of the microorganism to the dyes.